Optimisation of EOQ model with Weibull deterioration under crisp and fuzzy environment. (23rd May 2019) - Sayal, Anu; Singh, A.P.; Aggarwal, Deepak
Deterioration is an unavoidable condition prevalent in all spheres of the inventory system involving perishable goods. Though other factors are also responsible for the depletion of the level of the inventory but the effect of deterioration in this regards is quite high. In the present paper, we have considered the deterioration rate of the form of Weibull distribution and the demand rate is taken as a ramp type function of time, when the inventory system starts without any kind of shortage. We have developed a mechanism for the optimisation of the total cost of the EOQ inventory system in both crisp and fuzzy environment. An appropriate numerical example has been proposed in order to validate the model in both crisp and fuzzy system.